DIE ONTWIKKELING VAN DIE VROU AS SOLDAAT - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Through the ages there have been many examples of women soldiers. The legendary Jeanne d’Arc is quoted as a classic example, the Maid of Saragossa as an example wrt Spain and the legendary Queen Mantitisi of the Batlokwa (Sotho) tribe as another. Other countries such as Israel, for example, also had their share of women soldiers and examples of these are also discussed. Tendencies and developments in this field are analysed and the ultimate conclusion is reached that since the first World War, women have become more and more involved in military conflicts (albeit in a supporting role). America is quoted as an example of a country where many voices have been raised in favour of using women in a fighting capacity. The question now arises: will women eventually regain the role of Jeanne d’Arc of yore.